Are macrophages, myeloid derived suppressor cells and neutrophils mediators of local suppression in healthy and cancerous tissues in aging hosts? - Jackaman, Connie; Nelson, Delia (Elsevier, 2013)
Lung cancer is one of the commonest cancers worldwide and the incidence of malignant mesothelioma, caused by asbestos, is growing to global epidemic proportions. Standard chemotherapy only extends life expectancy in both cancers by, at best, a few years thus there is an urgent need for new treatment options. There are long latency periods of 30–45 years between asbestos exposure and development of diagnosable mesothelioma, and between cigarette smoking initiation and lung cancer diagnosis. Young people diagnosed with lung cancer or mesothelioma are rare. Children exposed to asbestos have a lower risk of developing mesothelioma compared to adults (Reid et al., 2007) and most cases occur in patients over 60 years. The mechanisms underlying this lengthy process are poorly understood. However, one contributing factor may be the declining immune function associated with aging, termed immunosenescence (Fulop et al., 2010). While, an age-related decline in T cell function is believed to contribute to increased cancer incidence in the elderly, the role of innate immune cells in cancer development is not so clear. Age-related immune dysfunction may be further compromised by tumor-associated factors and impact on therapeutic approaches involving the immune system, including standard chemotherapy. Yet preclinical studies of anti-cancer therapies are almost inevitably conducted in young adult animals with intact immunity, and elderly patients are often excluded from clinical trials due to toxicity concerns.